Mechanisms contributing to low orthostatic tolerance in women: the influence of oestradiol. (11th March 2013) - Wenner, Megan M.; Haddadin, Ala' S.; Taylor, Hugh S.; Stachenfeld, Nina S.
Key points The maintenance of blood pressure upon standing is accomplished through an integration of physiological systems. The inability to maintain blood pressure upon standing is called orthostatic intolerance and occurs more frequently in women than in men. Given that ovarian hormones fluctuate throughout the menstrual cycle, it is difficult to isolate the effects of oestradiol on cardiovascular control systems in humans. We utilize a novel study design in which we suppress endogenous ovarian hormones, then add back oestradiol to isolate its effects on blood pressure‐regulating systems. We show that women with low orthostatic tolerance have a lower vasoconstrictor response to gravitational stress and lower stroke volume in comparison to women with normal/high orthostatic tolerance. Oestradiol further suppresses the vasoconstrictor response to gravitational stress in women with low orthostatic tolerance; heart rate increases more to compensate for this impairment. These results help us to better understand why women are more susceptible to orthostatic intolerance and how oestradiol affects the regulation of blood pressure. Abstract The impact of 17β‐oestradiol (E2) exposure on autonomic control of orthostasis in young women is unclear. We tested the hypothesis that autonomic cardiovascular regulation is more sensitive to E2 exposure in women with low orthostatic tolerance. Women underwent an initial maximal lower body negative pressure (LBNP) test to place them into a low (LT, n= 7, 22 ± 1 years old, body mass index 22 ± 1 kg m−2) or a high orthostatic tolerance group (HT, n= 7, 22 ± 1 years old, body mass index 24 ± 1 kg m−2). We then suppressed endogenous reproductive hormone production using a gonadotrophin‐releasing hormone antagonist (GnRHant) for 10 days, with E2 administration during the last 7 days of GnRHant. We measured R–R interval and beat‐by‐beat blood pressure during the modified Oxford protocol, and changes in heart rate, blood pressure and forearm vascular resistance (FVR) during submaximal LBNP. During submaximal LBNP, FVR increased in HT (ANOVA P < 0.05) but not in LT (ANOVA P > 0.05), and stroke volume was lower in LT relative to HT at all levels of LBNP (P < 0.05). Compared with GnRHant, E2 administration shifted FVR lower in LT (ANOVA P < 0.05), with no effect in HT. Administration of E2 increased baroreflex control of heart rate (derived from the modified Oxford protocol) in LT (GnRHant 10.7 ± 2.5 ms mmHg−1 vs. E2 16.1 ± 2.4 ms mmHg−1, P < 0.05) but not in HT (GnRHant 13.4 ± 1.9 ms mmHg−1 vs. E2 15.3 ± 2.4 ms mmHg−1, n.s.). In conclusion, blunted peripheral vasoconstriction and lower stroke volume contribute to compromised orthostatic tolerance in women; this inability to vasoconstrict is further exacerbated by exposure to E2. Furthermore, E2 administration increases baroreflex‐mediated heart rate responses to orthostasis in low orthostatic tolerant women, which is likely to be a compensatory mechanism for the blunted peripheral vascular resistance and lower central volume.